Characterization of Pancreatic Cancer Cell Thermal Response to Heat Ablation or Cryoablation - Baumann, Kenneth W. (Technol Cancer Res Treat, 2016)
One of the most lethal carcinomas is pancreatic cancer. As standard treatment using chemotherapy and radiation has shown limited success, thermal regimens (cryotherapy or heat ablation) are emerging as viable alternatives. Although promising, our understanding of pancreatic cancer response to thermal ablation remains limited. In this study, we investigated the thermal responses of 2 pancreatic cancer cell lines in an effort to identify the minimum lethal temperature needed for complete cell death to provide guidance for in vivo applications. PANC-1 and BxPC-3 were frozen (−10°C to −25°C) or heated (45°C-50°C) in single and repeated exposure regimes. Posttreatment survival and recovery were analyzed using alamarBlue assay over a 7-day interval. Modes of cell death were assessed using fluorescence microscopy (calcein acetoxymethyl ester/propidium iodide) and flow cytometry (YO-PRO-1/propidium iodide). Freezing to −10°C resulted in minimal cell death. Exposure to −15°C had a mild impact on PANC-1 survival (93%), whereas BxPC-3 was more severely damaged (33%). Exposure to −20°C caused a significant reduction in viability (PANC-1 = 23%; BxPC-3 = 2%) whereas −25°C yielded complete death. Double freezing exposure was more effective than single exposure. Repeat exposure to −15°C resulted in complete death of BxPC-3, whereas −20°C severely impacted PANC-1 (7%). Heating to 45°C resulted in minimum cell death. Exposure to 48°C yielded a slight increase in cell loss (PANC-1 = 85%; BxPC-3 = 98%). Exposure to 50°C caused a significant decline (PANC-1 = 70%; BxPC-3 = 9%) with continued deterioration to 0%. Double heating to 45°C resulted in similar effects observed in single exposures, whereas repeated 48°C resulted in significant increases in cell death (PANC-1 = 68%; BxPC-3 = 29%). In conclusion, we observed that pancreatic cancer cells were completely destroyed at temperatures <−25°C or >50°C using single thermal exposures. Repeated exposures resulted in increased cell death at less extreme temperatures. Our data suggest that thermal ablation strategies (heat or cryoablation) may represent a viable technique for the treatment of pancreatic cancer.